Biological roles of Yin Yang 2: Its implications in physiological and pathological events. Issue 22 (23rd September 2020) - Li, Lang; Li, Yanjun; Timothy Sembiring Meliala, Ian; Kasim, Vivi; Wu, Shourong
Abstract: Yin yang 2 (YY2) is a multifunctional zinc finger protein that belongs to the yin yang (YY) family. YY2 has dual function in regulating gene expression, as it could act either as a transcriptional activator or as a repressor of its target genes. YY2 could regulate genes that have been previously identified as targets of yin yang 1 (YY1), another member of the YY family, by binding to their common binding sequences. However, recent studies revealed that YY2 also has its own specific binding sequences, leading to its particular biological functions distinct from those of YY1. Furthermore, they have different levels or even opposite regulatory effects on common target genes, suggesting the importance of balanced YY1 and YY2 regulations in maintaining proper cellular homeostasis and biological functions. Recent studies revealed that YY2 plays crucial roles in maintaining stemness and regulating differentiation potential of embryonic stem cells, as well as in the development of the brain, nervous and cardiovascular systems. YY2 expression is also closely related to diseases, as it could act as a tumour suppressor gene that regulates tumour cell proliferation and metastasis. Moreover, YY2 is also involved in immune regulation and immune surveillance. Herein, we summarize recent perspectives regarding the regulatory functions of YY2, as well as its biological functions and relation with diseases.